2022
DOI: 10.1080/09638288.2022.2030418
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and minimal detectable change of body-weight distribution and body sway between right and left brain-damaged patients at a chronic stage

Abstract: Reliability and minimal detectable change of body-weight distribution and body swaybetween right and left brain-damaged patients at a chronic stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Considering these differences, hemiparetic patients may have a different recovery depending on the side of the lesion, as shown in a cross-sectional study where patients with left hemiplegia had a faster improvement in the functional ambulation profile and the velocity compared to patients with right hemiplegia [ 14 ], followed by an observational study based on a retrospective chart review where patients had changes in the symmetry values and in the centre of pressure depending on the side of the lesion [ 15 ]; then, specifically looking at the right lesion, a recent trial assessed if stroke survivors with a right hemisphere injury showed poorer improvements in balance, and it found that they made more mistakes compared to patients with left injury when performing more complex tasks [ 16 ]. Lastly, it was also assessed that patients with a right lesion had a marginally higher minimal detectable change (MDC) in weight-bearing asymmetry compared to patients with a left lesion (7.3% and 5.4%, respectively), while the velocity of sway was 13 mm/s in patients with left lesions and 9 mm/s in patients with right lesions [ 17 ]. These findings suggest that it is necessary to perform different treatment methods and strategies that take into account the side of the stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Considering these differences, hemiparetic patients may have a different recovery depending on the side of the lesion, as shown in a cross-sectional study where patients with left hemiplegia had a faster improvement in the functional ambulation profile and the velocity compared to patients with right hemiplegia [ 14 ], followed by an observational study based on a retrospective chart review where patients had changes in the symmetry values and in the centre of pressure depending on the side of the lesion [ 15 ]; then, specifically looking at the right lesion, a recent trial assessed if stroke survivors with a right hemisphere injury showed poorer improvements in balance, and it found that they made more mistakes compared to patients with left injury when performing more complex tasks [ 16 ]. Lastly, it was also assessed that patients with a right lesion had a marginally higher minimal detectable change (MDC) in weight-bearing asymmetry compared to patients with a left lesion (7.3% and 5.4%, respectively), while the velocity of sway was 13 mm/s in patients with left lesions and 9 mm/s in patients with right lesions [ 17 ]. These findings suggest that it is necessary to perform different treatment methods and strategies that take into account the side of the stroke.…”
Section: Introductionmentioning
confidence: 99%